On the Use of Conjunctive Adverbs in Learners’ Academic Essays - Janulienė, Aušra; Dziedravičius, Justinas (Verbum, 2015)
[full article, abstract in English; abstract in Lithuanian]The aim of the present research was to analyze the usage of conjunctive adverbs in the university law students’ academic essays in their role to achieve cohesion, i.e. make the text comprehensible, logical and complete. The concept of cohesion has been defined and its different types explained. The subject of the paper was conjunctive adverbs as a sub-group of grammatical cohesion, so their classification based on their meaning and function was provided. According to the hypothesis of this paper, learners of English use various types of conjunctive adverbs to join certain parts of their academic essay together, provide background for their arguments, and produce a cohesive academic piece of writing. 88 law students’ academic essays have been collected and analysed with the focus on conjunctive adverbs: the area of their usage has been defined, the reasons for a particular usage have been given, faulty usage has been illustrated and interpreted, synonymous adverbs have been explained and separated. To determine the frequency of the adverbs, a corpus tool AntConc has been used and raw frequencies of the conjunctive adverbs have been accordingly provided. The overall results have shown that although conjunctive adverbs belong to only one area of grammatical cohesion, they have appeared in every essay under investigation and thus are a crucial device to achieve cohesion.
Keywords: learners’ language; academic writing; text cohesion; conjunctive adverbs